Lanesfield, Johnson County - Angles, Steven (Kansas State University, The Chapman Center for Rural Studies, 2012)
Lanesfield, Kansas was founded in honor of James Henry Lane, an infamous free-state leader, during a period of extreme violence and chaos. Lanesfield grew in the early years, but eventually disintegrated as people relocated closer to the railroad. This study includes a map of the area and extensive research on the development and downfall of Lanesfield, Kansas.
Steven Angles, “Lanesfield, Johnson County,” Chapman Center Research Collections,https://ccrsresearchcollections.omeka.net/items/show/72..
Keywords: anti-slavery; Bleeding Kansas; Bull Creek; James Henry Lane; Johnson County; Hibbard Post Office